Beta Diversity of Tenebrionid Beetles (Coleoptera, Tenebrionidae) in Ningxia Grasslands and Their Driving Factors - Changyu Xiong; Ziyu Cao; Haixiang Zhang; Ying Wang; Wei Sun; Chun Shi; Yifan Cui; Rong Zhang; Shuhua Wei (Biology)
This study explored the beta diversity patterns of tenebrionid beetles and their driving factors across four grassland types in Ningxia. A total of 32 monitoring sites were surveyed, capturing 5328 individuals from 47 tenebrionid species. Permutation multivariate dispersion (PERMDISP) and non-metric multidimensional scaling (NMDS) revealed significant differences in community composition among the four grassland types (Stress = 0.091). Beta diversity decomposition indicated that species replacement primarily drives beta diversity among four temperate grassland types. Canonical Correspondence Analysis (CCA) showed that mean temperature, field water holding capacity, total soil phosphorus, biomass of Asteraceae, biomass of Leguminosae, and frequency of Leguminosae significantly explained variations in dominant species abundance (p < 0.05). Mantel tests revealed that beta diversity was positively correlated with differences in mean temperature, field water holding capacity, total soil phosphorus, and Asteraceae biomass (p < 0.01), but negatively correlated with Leguminosae frequency (p < 0.05). Overall, daily mean temperature was the primary driver of diversity, with synergistic effects from climate, elevation, soil, and vegetation. This study provides a comprehensive analysis of environmental factors influencing tenebrionid diversity, offering insights for grassland biodiversity conservation.